The phospholipid membrane compositions of bacterial cells, cancer cell lines and biological samples from cancer patients. Issue 40 (28th September 2021) - Hilton, Kira L. F.; Manwani, Chandni; Boles, Jessica E.; White, Lisa J.; Ozturk, Sena; Garrett, Michelle D.; Hiscock, Jennifer R.
Abstract : This review acts as a repository and comparison of cell membrane phospholipid composition data collected from microbial and cancer fields. Abstract : While cancer now impacts the health and well-being of more of the human population than ever before, the exponential rise in antimicrobial resistant (AMR) bacterial infections means AMR is predicted to become one of the greatest future threats to human health. It is therefore vital that novel therapeutic strategies are developed that can be used in the treatment of both cancer and AMR infections. Whether the target of a therapeutic agent be inside the cell or in the cell membrane, it must either interact with or cross this phospholipid barrier to elicit the desired cellular effect. Here we summarise findings from published research into the phospholipid membrane composition of bacterial and cancer cell lines and biological samples from cancer patients. These data not only highlight key differences in the membrane composition of these biological samples, but also the methods used to elucidate and report the results of this analogous research between the microbial and cancer fields.